Bile duct injuries during laparoscopic cholecystectomy - Vidal, Gustavo (2014)
Introduction: Most studies on the subject have shown that bile duct injury (BDI) occurs more commonly in laparoscopic cholecystectomy than in the open procedure. Even though there is a certain awareness of this problem, more attention should be paid to early recognition and prevention of BDI. Methods: A review of English language literature from the last 15 years on the occurrence, management and prevention of bile duct injury was performed. Older benchmark articles on the subject were also included. Data resources: PubMed and Scopus database research. Results: Approximately 1500 articles came as a result of searching the keywords “bile duct injuries”and “laparoscopic cholecystectomy”. A selection of 68 articles was made based on the abstract, directed according the subject of interest for the discussion of this review and 49 were included on the bibliography, for being considered of most interest. Conclusions: Bile duct injury could be avoided by proper and precise anatomical identification and careful dissection. Intraoperative cholangiography helps in decreasing incidence and early recognition, in case of an injury. Improved outcome is related to early detection and repair.